A Comprehensive Meta-Analysis of MicroRNAs for Predicting Colorectal Cancer. Issue 9 (March 2016) - Yan, Lin; Zhao, Wenhua; Yu, Haihua; Wang, Yansen; Liu, Yuanshui; Xie, Chao
Abstract : Abstract: Colorectal cancer (CRC) has been defined as a common malignancy due to its prevailing incidence in both males and females. Recently, the intrinsic value of microRNAs (miRNAs) with respect to early cancer diagnosis has been contentious as the diagnostic accuracy of miRNAs significantly varied across different studies. As a result of this, this pioneer meta-analysis was proposed to address this issue. Qualified studies were obtained through electronic systematical searching in Medline, Embase, and PubMed. On the basis of the random-effects model, we calculated the pooled sensitivity (SEN), specificity (SPE), and area under the receiver operating characteristics curve (AUC) to assess the diagnostic accuracy of miRNAs. Subgroup analysis and meta-regression were implemented to determine how different confounding factors affect the overall diagnostic accuracy which were considered important sources of heterogeneity. All the statistical analyses were conducted with R 3.2.1 software. We incorporated 103 studies from 36 articles with a total of 3124 CRC patients and 2579 healthy individuals. MiRNAs have a good performance with the following pooled estimates: SEN = 0.769 (95% CI = 0.733–0.802), SPE = 0.806 (95% CI = 0.781–0.829), AUC = 0.857, and partial AUC = 0.773. As suggested by subgroup analyses and meta-regression, multiple miRNAs appeared to be more favorable than single miRNA (AUC: 0.918 > 0.813, partial AUC: 0.848 > 0.701, sensitivity = 0.853 > 0.718, specificity = 0.860 > 0.772). Compared with samples of plasma, blood, tissue, and feces, miRNA obtained from serum samples were more powerful for detecting CRC particularly in Asian. Our study provided exclusive evidence that multiple miRNAs extracted from serum samples had superior diagnostic performance over single miRNA for screening CRC. Therefore, this approach that is characterized by high specificity and noninvasive nature may assist in early diagnosis of CRC particularly in Asian. Abstract : Supplemental Digital Content is available in the text